2021
DOI: 10.3390/polym14010038
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extrinsic Factors on the Mechanical Behavior and Structure of Elastic Dental Ligatures and Chains

Abstract: Force provided by elastomers used in orthodontics can be affected by several factors present in the oral cavity. The aim of our study was to investigate the role of mouthwashes, toothbrushing, and smoking in the force decay of such elastomers. Tensile strength, changes in the force continuously exerted, and force decay of elastic chains (Ortho Organizer and Masel Short Power Chain) and elastic ligatures (Dentaurum and Masel) by two separate manufacturers were measured. Measurements were initially made on untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[ 34 ] Studies have looked into the impacts of simulated saliva environments, pH, and thermocycling, in an effort to model different oral environments, on force degradation. [ 34 35 36 37 ] The simplest formulation of artificial saliva is 0.09% aqueous sodium chloride, which is frequently employed in experiments simulating the intraoral environment. In general, the data showed that after elastics were subjected to experimental circumstances, force significantly relaxed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 34 ] Studies have looked into the impacts of simulated saliva environments, pH, and thermocycling, in an effort to model different oral environments, on force degradation. [ 34 35 36 37 ] The simplest formulation of artificial saliva is 0.09% aqueous sodium chloride, which is frequently employed in experiments simulating the intraoral environment. In general, the data showed that after elastics were subjected to experimental circumstances, force significantly relaxed.…”
Section: Discussionmentioning
confidence: 99%
“…During clinical use, orthodontic elastic bands are believed to degrade mostly as a result of mechanical forces. [ 37 ] Leachable moieties, however, have been isolated from a few orthodontic elastic bands, and their rising concentrations in solution correlated with a gradual loss of force. [ 38 ] The majority of the experiments on the deterioration of orthodontic elastic materials have been done in artificial saliva or air, although this topic has been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have shown increased force decay, such as the study of Behnaz et al on bleaching and sodium fluoride mouthwashes, recommended using them for a short period of time [16]. However, other studies demonstrated that there was no relationship between force loss and substances present in mouth rinses [1,17]. Takeda et al established that CPC had anti-SARS-CoV-2 actions without altering the virus envelope, and low quantities inhibit the infectivity of human-isolated SARS-CoV-2 strains in saliva [18].…”
Section: Introductionmentioning
confidence: 99%